The role of gut microbiome modulation in the management of neurodevelopmental disorders: current evidence and future directions - Protić, Dragana; Nikolić, Vladimir; Stojković, Maja (Medicinski podmladak, 2025)
Neurodevelopmental disorders (NDDs), including autism spectrum disorder (ASD), attention-deficit/hyperactivity disorder (ADHD), and other cognitive and behavioral impairments, are increasing globally, placing significant burdens on individuals and healthcare systems. Traditional therapeutic strategies, primarily pharmacologic and behavioral, offer limited efficacy and often fail to address the multifactorial etiology of these conditions. Recent advances in microbiome research highlight the gut microbiota as a potential modulator of brain function via the microbiota–gut–brain axis (MGBA). This bidirectional network influences neurodevelopment through neural, immune, endocrine, and metabolic pathways. Dysbiosis, or microbial imbalance, has been consistently reported in individuals with NDDs, particularly in ASD and ADHD, correlating with symptom severity and gastrointestinal comorbidities. Emerging interventions aimed at restoring microbial balance, such as probiotics, prebiotics, synbiotics, faecal microbiota transplantation (FMT), and dietary modifications - demonstrate potential in modulating behaviour and cognition. However, the current evidence is limited by small sample sizes, heterogeneous methodologies, and a lack of long-term follow-up. This mini-review synthesizes current findings on the role of gut microbiome modulation in NDDs, evaluates the therapeutic efficacy of microbiome-based interventions, and discusses future directions, including personalized microbiome-targeted strategies and the need for robust randomized controlled trials.